Modelling the probability of lightning-induced forest fire occurrence in the province of León (NW Spain) - Castedo-Dorado, Fernando; Rodríguez-Pérez, José Ramón; Marcos-Menéndez, José Luis; Álvarez-Taboada, Mª Flor (Forest Systems, 2011)
Spatial relationships between lightning-induced forest fires and topography, vegetation, climate and lightning characteristics were analyzed in the province of León (NW Spain). The study was based on reported lightning-induced forest fires in the period 2002-2007. A statistical model based on logistic regression was developed to estimate the probability of occurrence of a lightning-induced fire in a 3 x 3 km grid. The importance of accurate location of the ignition point was also investigated in order to evaluate the sensitivity of the model developed to uncertainty of the location. The model developed with accurate ignition point data showed a better predictive ability than the model constructed with all the ignition points available. The former model was therefore selected for long-term prediction of the occurrence of lightning-induced fires in the province. According to this model, the probability of a forest stand being affected by lightning-induced fire increased with decreasing altitude, and when there was a high proportion of coniferous species in the stand, a high percentage of lightning strikes in forest areas and a high number of dry storm days in the area. Although the model has not been validated, the results can be considered spatially robust because it shows good classification ability and the predicted spatial probability distribution is consistent with the observed historical fire records. The model will be useful in the spatially explicit assessment of fire risk, the planning and coordination of regional efforts to identify areas at greatest risk, and in designing long-term wildfire management strategies.